Computer Self-Efficacy and Effectiveness of Quipper Learning Management System (American Journal of Smart Technology and Solutions, 2024)
This quantitative study aimed to determine the relationship between computer self-efficacy and the effectiveness of the Quipper learning management system among senior high school students. The study utilized a descriptive-correlational design. Data on computer self-efficacy and Quipper LMS effectiveness were collected from 290 senior high school students using survey questionnaires. The results showed high overall computer self-efficacy (M=4.18, SD=0.652) and high effectiveness of the Quipper LMS (M=3.97, SD=0.622) among students. A significant positive correlation (r=0.414, p=.000) between computer self-efficacy and Quipper LMS effectiveness indicates a low positive relationship between the two variables. Computer self-efficacy has a direct relationship with the effectiveness of the Quipper LMS. As computer self-efficacy increases, the effectiveness of the Quipper LMS also increases among senior high school students.